Comparing quality of life instruments: Sizing them up versus pediatric quality of life inventory and Kid-KINDL - Chung Ying Lin (Wolters Kluwer Medknow Publications, 2018)
Introduction: Children with overweight or obesity are very likely to experience health problems including low levels of psychological well-being and impaired quality of life (QoL). Given that the importance of QoL includes policymaking measuring QoL is especially crucial. Therefore, comparing generic (Kid-KINDL and Pediatric QoL Inventory [PedsQL]) and weight-related (Sizing Them Up) measures could provide insights for healthcare providers to decide how and when to use which QoL instrument. Methods: I recruited 199 school children studied between 3rd and 6th grades from 11 schools in Southern Taiwan, and all the children completed child depression inventory (for depression) and Rosenberg self-esteem scale (for self-esteem); one of their parents completed Sizing Them Up, PedsQL, and Kid-KINDL. Results: I constructed structural equation modeling to investigate the associations between these instruments, and the results indicated that self-esteem had the strongest relationship with Kid-KINDL; weight had the strongest relationship with Sizing Them Up. Moreover, both PedsQL and Kid-KINDL could observe the depression among children. Conclusion: Healthcare providers may have insights to select appropriate measure to assess QoL for overweight/obese children according to my findings.